Pengaruh Latihan Mckenzie Terhadap Derajat Nyeri Pada Dewasa Dengan Non-Spesifik Kronik Nyeri Punggung Bawah - Mohammad Ali; Abdurahman Berbudi B L; Firdausa Febriana (Jurnal Fisioterapi dan Kesehatan Indonesia, 2021)
Background : Low Back Pain is a musculosceletal disorders that found in 15-45% of adults every year. McKenzie method is one of intervention that can be used to handle this case. McKenzie method is an active therapy that involves repetitive movements or maintaining position with aims for reducing pain, disability and increasing spinal mobility. Objective : This study aims to determine the effect of McKenzie Exercise on pain level in the adults with non-specific chronic low back pain. Method : This study design is literature studies with a systematic approach. Result: 343 literature was filtered from online search. 10 literature were obtained based on inclusion and exclusion criteria and by using the initial and methodological selection questionnaire. 3 literature were indicate duplication. 7 elidgible literature were obtained; 6 literature are Randomized Controlled Trial, 1 literature is Experimental Study Design. The entire literature shows there is a change in pain intensity after doing McKenzie's exercise in adults with non-specific chronic low back pain. Conclusion : McKenzie's exercise effective for decreasing pain intensity in adults with Non-Specific Chronic Low Back Pain. The most effective dose is 1 hour exercise per session in 1 day, every day for 20 consecutive days.